Strengthening Online Marketing and Product Innovation for The "Nglarisi Jogja" Msme’s Community - Candra Asmarawan; Audita Nuvriasari; Gumirlang Wicaksono; Wanda Siahaan; Novita Ariani (IMPACTS: International Journal of Empowerment and Community Services, 2022)
"Ngelarisi UMKM Jogja" is a Community of Micro, Small and Medium Enterprises (MSMEs) located in the city of Jogja with 80 business members. This community is a place for MSMEs actors to exchange information and help each other promote MSMEs products. Business fields in this community include culinary, craft, services and fashion. Facing increasingly fierce business competition, community members must strive to attract consumer buying interest. However, there are a number of obstacles faced by community members. These obstacles are: (1) Not optimal use of social media as a means of online promotion for MSMEs products. This is due to the limited knowledge of members, especially the middle-aged in operating social media, (2) Lack of product innovation in MSMEs so that it is less attractive to consumer buying. The programs implemented to overcome these problems are: (1). provide training using social media. Especially Instagram, Facebook and features like snap stories and reels, (2). Conduct product innovation with the aim of increasing the attractiveness and increasing the economic value of the product. The methods used in this activity are: training for the use of social media and assistance in product innovation. The achievements of this activity are: partners can use content on social media to market MSMEs products, (2). increasing product variants through product innovation in the form of hampers and parcels.